Exploring Livelihoods of Urban Women Traders in the Context of Socio-Economic And Political Crisis: Evidence From Harare, Zimbabwe (Global Journal of Human-Social Science, 2014)
The Zimbabwean crisis has involved massive downsizing of the economy and high rate of unemployment levels particularly in urban areas. Urban life has become increasingly unbearable for many poor urban households. Consequently, informal economic activities have blossomed and are making significant contributions to household income and livelihoods. The role of women in the informal economy is particularly pronounced. This paper examines the livelihood strategies and sources of income for women traders at Magaba. The empirical findings identified and unpacked diverse livelihood activities and strategies and the resources (or assets) that women deploy in constructing urban livelihoods. Though their livelihood portfolios complement any earnings from formal employment by household members and though they contribute to their household's sustenance, there are a number of daily challenges which they face in their trading activities and which they seek to counteract through a range of often ingenious coping mechanisms. These findings were projected through a genre of qualitative and quantitative techniques. (Sustainable livelihoods, livelihoods, livelihood strategies, coping mechanisms).